2016
DOI: 10.1093/infdis/jiw160
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Independent Restriction of Pneumococcal Density by Mucosal Adjuvant Cholera Toxin Subunit B

Abstract: For many bacterial respiratory infections, development of (severe) disease is preceded by asymptomatic colonization of the upper airways. For Streptococcus pneumoniae, the transition to severe lower respiratory tract infection is associated with an increase in nasopharyngeal colonization density. Insight into how the mucosal immune system restricts colonization may provide new strategies to prevent clinical symptoms. Several studies have provided indirect evidence that the mucosal adjuvant cholera toxin subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
2
9
0
1
Order By: Relevance
“…Of note, Xue et al also demonstrated that the mucosal group immunized with an adjuvant elicited a greater response than the group without adjuvant. Our finding of rapid clearance of GBS from both the control and GBS-immunized mice via the intramuscular route demonstrate a potential role for systemic adjuvant in GBS colonization clearance, a non-specific effect shown by other groups [49]. …”
Section: Discussionsupporting
confidence: 56%
“…Of note, Xue et al also demonstrated that the mucosal group immunized with an adjuvant elicited a greater response than the group without adjuvant. Our finding of rapid clearance of GBS from both the control and GBS-immunized mice via the intramuscular route demonstrate a potential role for systemic adjuvant in GBS colonization clearance, a non-specific effect shown by other groups [49]. …”
Section: Discussionsupporting
confidence: 56%
“…This non-specific immunity against pneumococcal colonization in mice was recently associated with the activation of local innate response, involving activation of the caspase-1/11 inflammasome, mucosal T cells and macrophages [35]. An increase in IL-1β and macrophages was observed in the nasal tissue of animals inoculated with CTB.…”
Section: Discussionmentioning
confidence: 99%
“…S4B), suggesting that IL-17A may contribute to the nonspecific decrease in pneumococcal loads. Mucosal adjuvants such as cholera toxin subunit B (CTB) and cholera toxin (CT) were also described to reduce pneumococcal colonization in a nonspecific manner, although the underlying mechanisms may differ (23,24). The nonspecific increase in the IL-17A concentration might be derived from (25,26).…”
Section: Figmentioning
confidence: 99%